Narrative Minimalism and Symbolism in Ernest Hemingway’s The Old Man and the Sea - Neloy, Nowshad Hasan; Minhajul Islam (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
The Old Man and the Sea (1952) is the magnum opus of Ernest Hemingway. This novella not only presents Hemingway's distinctive narrative style but also engages rich symbolism to convey deeper meanings. It serves as a testament to the power of storytelling, where every word and symbol contributes to a greater understanding of our shared experiences. This paper aims at investigating Hemingway's minimalist narrative techniques, particularly his use of simple, concise language, and rich symbolism embedded in the text. Through an analysis of both stylistic and thematic elements, this study aims to shed light on characters and themes present in the novella. To conduct the research, a qualitative approach was chosen. The data analysis was conducted through close reading. This involved a detailed examination of the text’s language, structure, and characterization. Findings from this study confirmed that The Old Man and the Sea is a novella built on simple but powerful dialogue using concise language and rich symbols that enrich the story's meaning.